A New Two-Parameter Lindley Distribution - Shanker, Rama; Rahman, Umme Habibah (Nepal Journal of Mathematical Sciences, 2020)
In this paper, a new two-parameter Lindley distribution has been proposed. Descriptive statistical properties along with order statistics, Fisher information matrix and confidence interval of the proposed distribution have been discussed. Parameters are estimated by the method of Maximum Likelihood estimation. A real lifetime data has been presented to test the goodness of fit of the proposed distribution over other one parameter and two –parameter Lindley family of distributions.